Effect of Housing Types on Growth, Feeding, Physical Activity, and Anxiety-Like Behavior in Male Sprague-Dawley Rats - Teske, Jennifer A.; Perez-Leighton, Claudio Esteban; Noble, Emily E.; Wang, Chuanfeng; Billington, Charles J.; Kotz, Catherine M. (Frontiers in Nutrition, 2016)
Background: Animal welfare and accurate data collection are equally important in rodent research. Housing influences study outcomes and can challenge studies that monitor feeding, so housing choice needs to be evidence-based. The goal of these studies was to 1) compare established measures of well-being between rodents housed in wire grid-bottom floors with a resting platform compared to solid-bottom floors with bedding and 2) determine whether presence of a chewable device (Nylabone) affects orexin-A-induced hyperphagia. Methods: Rodents were crossed over to the alternate housing twice after two-week periods. Time required to complete food intake measurements was recorded as an indicator of feasibility. Food intake stimulated by orexin-A was compared with and without the Nylabone. Blood corticosterone and hypothalamic BDNF were assessed. Results: Housing had no effect on growth, energy expenditure, corticosterone, hypothalamic BDNF, behavior and anxiety measures. Food intake was disrupted after housing cross-over. Time required to complete food intake measurements was significantly higher for solid-bottom bedded cages. The Nylabone had no effect on orexin-A-stimulated feeding. Conclusion: Well-being is not significantly different between rodents housed on grid-bottom floors and those in solid-bottom bedded cages based on overall growth and feeding, but alternating between housing confounds measures of feeding.